Silicon as a biostimulant in cocoa (Theobroma cacao L.) cultivation and biological control agent for Moniliophthora roreri (TERRA LATINOAMERICANA, 2024)
The cocoa crop is very susceptible to nutritional deficiencies and moniliasis caused by the phytopathogen Moniliophthora roreri. One of the alternatives to synthetic chemicals are silicon (Si) based compounds. In the present investigation, the effect of silicon as a biostimulant in the cocoa (Theobroma cacao L.) crop and as a biological control agent for Moniliophthora roreri was evaluated. Five Si treatments were used in the experiment: T1 (4.00 kg ha-1), T2 (3.00 kg ha-1), T3 (2.00 kg ha-1) and T4 (1.5 kg ha-1) and one treatment control (without application). The production indicators, number of healthy ears, fresh and dry weight of almonds, dry weight of 100 almonds and crop yield were determined. In addition, the incidence and severity of the disease at 60, 120 and 180 days after the application of Si and the efficiency of the treatments. Regarding production variables, the best treatment was T1. All Si treatments were superior to the control in the production variables. The highest yield was obtained with the T1 treatment with 2.23 t ha-1. The best treatment was T1 in the control of the disease, the incidence and severity decreased by more than 50%. The control treatment T5 without application of Si, obtained the highest incidence and severity with 62.12% and 4.50 respectively, in addition to the lowest results in the variables of production and yield of the crop with 0.78 t ha-1.
Keywords: treatment ef ficiency; disease incidence; performance; disease severity